Manajemen Pembiayaan di SD Negeri Godean 1 Kapanewon Godean Kabupaten Sleman - Salindri, Anistya Ori (Media Manajemen Pendidikan, 2024)
This study aims to analyze financing management in SD Negeri Godean 1 Kapanewon Godean, Sleman Regency. This research is qualitative research with a type and descriptive approach to analysis. Data sources used in this study through data collection using interview methods, non-participant observation, and documentation. Testing the validity of data with credibility tests (internal validity) and conducting data analysis and interpretation techniques with the process of data reduction, data presentation, and conclusion drawing or verification. The results showed that the management of education financing at SD Negeri Godean 1 was carried out well. Financing activities at SD Negeri Godean 1 have been integrated between one application and other applications such as SIPLAH, SILABOSDA, and ARKAS. This shows transparency and accountability. The implementation of education financing has been achieved as planned, especially in the use of funding sources although sometimes there are delays in the distribution of education funds.